The Effectiveness of Illustrated Word Cards in Increasing Reading Interest of Children at Al-Jami'atul Amaliyah Gerumpung Kindergarten, Sepit Village, Academic Year 2022/2023 - Syarifatul Munawarah; Ahmad Izzuddin; Yuliana Susanti (Formad English Foundation NTB-Jakarta, 2024)
The aim of this research is to determine the effectiveness of illustrated word card media in increasing the reading interest of children at Al-Jam’iyatul Amaliyah Gerumpung Kindergarten in Sepit Village for the Academic Year 2022/2023. The research method used is descriptive qualitative with a survey research design. This study was conducted at Al-Jam‟iyatul Amaliyah Gerumpung Kindergarten in Sepit Village, Keruak Sub-district, East Lombok, West Nusa Tenggara. Three data collection techniques were employed: observation, interviews, and documentation. The data analysis technique used is descriptive analysis with components of data reduction, data presentation, and verification. The research results indicate that illustrated word card media has a positive impact on increasing children's reading interest at Al-Jamiatul Amaliyah Gerumpung Kindergarten in Sepit Village. This is evident from the responses of 5 out of 6 teachers, representing 83.33%, who have a positive outlook. Out of the total 20 participating students, 14 students showed a positive response, accounting for 70%. Additionally, among the 15 parents participating in this study, 12 respondents, or 80%, expressed a positive perspective. Therefore, it can be concluded that illustrated word card media is effective in enhancing the reading interest of children at Al-Jam’iyatul Amaliyah Gerumpung Kindergarten.